The secret history of home economics : how trailblazing women harnessed the power of home and changed the way we live - Dreilinger, Danielle (np np, 2021)
"The surprising, often fiercely feminist, always fascinating, yet barely known, history of home economics. The term "home economics" may conjure traumatic memories of lopsided hand-sewn pillows or sunken cakes. But obscured by common conception is the story of the revolutionary science of better living. The field exploded opportunities for women in the twentieth century by reducing domestic work and providing jobs as professors, engineers, chemists, and businesspeople that were otherwise foreclosed. In The Secret History of Home Economics, Danielle Dreilinger traces the field's history from small farms to the White House, from Victorian suffragists to Palo Alto techies. Home economics followed the currents of American culture even as it shaped them; Dreilinger brings forward the racism within the movement along with the strides taken by Black women who were influential leaders and innovators. She also looks at the personal lives of home economics' women, as they chose being single, shared lives with women, or tried for egalitarian marriages. This groundbreaking and engaging history restores a maligned subject to its rightful importance"--
Keywords: Home economists -- Biography; Housekeepers -- Biography; Women scientists -- Biography; Home economics -- History